ANALISIS PENGUKURAN KUALITAS WEBSITE CAKRAWALAMEDIA.CO.ID DENGAN MENGGUNAKAN METODE WEBQUAL 4.0 - Firdaus, Muhammad Rifqi; Purnia, Dini Silvi; Handayani, Kartika; Julianto, Muhamad Fahmi (JTIK (Jurnal Teknik Informatika Kaputama), 2020)
The development of Information Technology has triggered the emergence of many online media. The cakrawalamedia.co.id website is an online media portal that utilizes these updates. Cakrawalamedia.co.id presents the focus of news around West Java especially the City of Tasikmalaya. The problem related to this research is whether the quality of cakrawalamedia.co.id website influences the readers' satisfaction. This study focuses on user satisfaction with the webqual method which consists of 3 variables, namely usability, information quality and interaction quality. The data used are primary data, namely by distributing questionnaires using a Likert scale with 22 questions to 133 respondents. Data obtained and processed using multiple linear regression analysis techniques using SPSS 16 software. Based on webqual variables, the results of the analysis state the quality of usability, information quality and interaction quality affect user satisfaction.